Precarious Intellectuals: The Freelance Academic in Malaysian Higher Education - Alicia Izharuddin (Kajian Malaysia, 2018)
What is the impact of the rising class of the academic precariat – defined as academic workers contracted to teach and conduct research on short-term, zerohour contracts – on Malaysia's rapid industrialisation of higher education? This article seeks to illuminate the employment pattern of this growing class of insecure academic labour at a time when there is a decline in tenured appointments and academic positions for new PhD graduates in Malaysia. The work environment of the academic precariat is characterised as flexible at best and exploitative at worst; an average academic precariat may experience a drop in wages commensurable with their qualification and experience, lack of employment benefits and office hours, and "docility" under the disciplinary management of a neoliberal institution. This article also seeks a sensitive reading of how freelance academics understand themselves by highlighting their affective or emotional labour and whose experiences are specifically shaped by insecurity, vulnerability and uncertainty. Taking a sociological approach to examining this phenomenon, this article argues that the rise of the academic precariat can be attributed to the discursive climate within and at the peripheries of Malaysian higher education that operates alongside the restructuring of funds into higher institutions of learning. Such a discursive climate surrounds the unstable semantic reproduction of the designation "academic" and its catch-all usage to describe individuals within and at the peripheries of academia. Arguing that the rise of the academic precariat is a bleak indication of the state of higher education in Malaysia, this article closes with strategies for mobilising resistance and marshalling support through the strengthening of unions for full-time, part-time and freelance academics.